DAMPAK MEDIA SOSIAL TERHADAP KOMUNIKASI INTERPERSONAL MAHASISWA INSTITUT UMMUL QURO BOGOR - Akhmad Saoqillah; Restu Nada Siti Wardah (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2018)
Social media is a new type of media that has emerged along with the development of information technology recently. Social media has various types. For example, there are Facebook, Instagram, Twitter, WhatsApp and others. Social media was originally created to make it easier for humans to communicate, human communication, especially interpersonal communication, is much easier with the presence of social media. With social media, interpersonal communication relationships can be done only with gadgets, but this raises a sense of concern from social media users regarding interpersonal relationships. This study aims to examine the impact of social media on interpersonal communication of students at the Institute of Ummul Quro al-Islam Bogor. This research method using literature study method. The data needed in this writing is obtained through books, journals and previous research. The results showed that social media changed the interpersonal communication relationship, especially among students, that is, students often looked busy looking at their gadgets rather than chatting with people around them